Leptospirosis health intervention module effect on knowledge, attitude, belief, and practice among wet market workers in Northeastern Malaysia: an intervention study - Ab Rahman, Mas Harithulfadhli Agus; Mohd Hairon, Suhaily; Awang Hamat, Rukman; Tengku Jamaluddin, Tengku Zetty Maztura; Shafei, Mohd Nazri; Idris, Norazlin; Osman, Malina; Sukeri, Surianti; A. Wahab, Zainudin; Wan Mohammad, Wan Mohd Zahiruddin; Idris, Zawaha; Daud, Aziah (Multidisciplinary Digital Publishing Institute, 2018)
Leptospirosis is an infectious disease which can be prevented by increasing awareness and promoting preventive health behaviours among high risk groups including wet market workers. Thus, the aim of this study was to determine the effectiveness of Leptospirosis Health Intervention Program (LHIP) in improving knowledge, attitude, belief and practice towards leptospirosis among wet market workers in Kelantan. This intervention study was conducted in two main wet markets in Kelantan involving 116 participants in each control and intervention groups. The health education intervention was based on Leptospirosis Health Intervention Module. The knowledge, attitude, belief and practice scores were measured before and six weeks after the intervention to examine the effect of the program. The results showed that knowledge (p < 0.001), attitude (p = 0.001), belief (p < 0.001) and practice (p < 0.001) scores changes were significantly higher in the intervention group compared to the control group. The adjusted mean differences were 12.93 (95% CI: 8.47, 17.39) for knowledge, 5.55 (95% CI: 2.28, 8.81) for attitude, 7.21 (95% CI: 3.43, 10.99) for belief and 7.35 (95% CI: 3.64, 11.05) for practice scores. Leptospirosis Health Intervention Program was an effective health educational tools to improve awareness and preventive behaviours among risk groups such as wet market workers.